The Impact of Director’s Multiple Positions on Investment Efficiency Decisions - Selano, Elysabet Christy Diandra (Riset Akuntansi dan Keuangan Indonesia, 2021)
There are differences in research results regarding the impact of a director’s busyness due to multiple positions, so this study aims to examine the relationship between director busyness and investment efficiency decisions from the perspective of the upper echelons theory. This study uses regression analysis and moderated regression analysis. The sample used is mining companies listed on the IDX in 2015- 2019. The results of this study indicate that they take sides on a reputation hypothesis, that a director who has more than one position at the same time influences the investment decisions that are made. However, when the complexity of the company is included in the regression model, it turns out that it can moderate the relationship between director busyness and investment efficiency decisions.